Application of ANN in Prediction of Vibration Caused By Blast Operation, Case Study Shur River Dam - Mohammad reza Motahari; Amin Vafaei (مهندسی و مدیریت ساخت)
Ballast shaking is one of the most significant adverse effects of explosion operations in construction projects and surface mines, and in case of control, it will lead to extensive damage to the surrounding structure. Therefore, accurate prediction of these vibrations is essential in minimizing its environmental effects. The goal of the current paper is to investigate and predict the results of the ballast operation on the Shur River dam structure. The application of the ANN as a powerful tool in predicting vibration generated from explosion operations has been studied. In addition to the ANN, experimental models have been used for this work. Different statistical criteria such as RMSE have been used to evaluate the performance of the proposed models in predicting vibrations. The results indicate that the values by the ANN are closer to real values and ANN has a much higher accuracy than other empirical models in predicting the vibration caused by the explosion operation.